Evaluation of mango residues to produce hyaluronic acid by Streptococcus zooepidemicus - Contreras Mendoza, Jesús; Arriola Guevara, Enrique; Suarez Hernández, Luis Antonio; Toriz, Guillermo; Guatemala-Morales, Guadalupe María; Corona-González, Rosa Isela (Folia microbiologica, 2024)
Mango processing generates significant amounts of residues (35-65%) that may represent environmental problems owed to improper disposal. The use of mango byproducts as substrates to produce hyaluronic acid (HA) is an attractive alternative to reduce the cost of substrate. In this study, we evaluated the potential of hydrolyzates from mango peels and seeds to produce HA by Streptococcus equi. subsp. zooepidemicus. The physicochemical characterization of mango residues showed that the seeds contain a higher amount of holocellulose (cellulose and hemicellulose), which amounts 54.2% (w/w) whereas it only represents 15.5% (w/w) in the peels. Mango peels, however, are composed mainly of hot water-extractives (62% w/w, that include sucrose, fructose, glucose and organic acids). A higher concentration of monosaccharides (39.8 g/L) was obtained from the enzymatic hydrolysis (with Macerex) of peels as compared to seeds (24.8 g/L with Celuzyme). From mango peels, hydrolyzates were obtained 0.6 g/L HA, while 0.9 g/L HA were obtained with hydrolyzates from mango seeds. These results demonstrate that mango byproducts have the potential to be used for production of HA.
Keywords: Hydrolysis; Hyaluronic Acid; Monosaccharides; monosacharidy; Streptococcus equi; Mangifera; celulosa; hydrolýza; Cellulose; kyselina hyaluronová; fermentace; Seeds; Fermentation; semena rostlinná